Peculiarities and Prospects of Bank Lending to the Agriculture at the Current Phase of Economic Development in Ukraine - Т. BONDARUK; М. LUKASHUK (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
It is demonstrated that the domestic agricultural sector continues to be underfunded in spite of special lending programs for agricultural producers implemented by banks and stimuli provided by international financial organizations to agricultural producers to make them introduce energy saving measures. The research objective is to review the current situation with bank lending of the agricultural sector in Ukraine and determine its main problems and prospects. The following research methods were used: induction, deduction, system approach, statistical analysis, logical generalization, graphical method.   It is shown that the bank lending in Ukraine is operating now under the pressures of the financial globalization processes and in the post-crisis condition of the bank sector, high risks and information asymmetry characterized by lack of complete and reliable information about the factors underlying business operation in various economic sectors, required for the assessment of the borrowers’ creditworthiness, and by inefficient financial and credit instruments.    A review of global practices shows that in most part of foreign countries governments support lending to agricultural producers through budget preferences or limitations imposed on the banks that can lend agricultural producers, with laying down a requirement that the loans provided to the agricultural sector must be the cheapest ones. Lending of agricultural producers in European countries is most often carried out by cooperative banks, with mortgage of lands being the main form of long-term lending. Considering the European practice, creating a specialized agrarian bank or applying economic stimuli to banks engaged in lending of the agricultural sector may be a solution of lending problems in Ukraine.The study of specific features of bank lending to the agricultural sector at the current phase of economic development in Ukraine confirms the need for further with scientific justifications of the government support to lending processes in the agricultural sector.